Sarawak Libraries Collaboration Initiatives: In The Aspirations Towards Bridging Knowledge Divide And Sustainability / Imilia Ibrahim, Margaret Simeng and Valentino Abu Bakar - Ibrahim, Imilia; Simeng, Margaret; Abu Bakar, Valentino (2011)
The aim of this paper is to discuss and highlight collaboration efforts done by libraries generally in Borneo and specifically in Sarawak. There are many initiatives by libraries and other information professional planned and executed in Sarawak with purpose to ensure the information managers community could maintain and enhance their knowledge and skills and at the same time could increase awareness and access towards information among library users.In discussing issues in smart partnership, this paper is prepared to answer two basic questions. The first question is what are the smart partnership initiatives joined by libraries in Sarawak and the second question would be what are the challenges and opportunities faced by libraries in Sarawak with regards to smart partnership. The method used in this paper is case study. The Centre for Academic Information Services, Universiti Malaysia Sarawak has been actively involved in many smart partnership initiatives. Therefore this paper will look at all the initiatives joined and initiated by the library to identify answers to the above research questions.Smart partnership allows libraries to be involved in an intellectual collaboration as well as giving them opportunities to share resources thus giving the opportunities to save resources.